- #1

- 1,344

- 30

## Main Question or Discussion Point

In page 39, Peskin and Schroeder write that (3.15) ##{\bf{J}}={\bf{x}} \times{\bf{p}}= {\bf{x}}\times(-i \nabla) ## can be used to derive the Lorentz algebra (3.12) for the rotation group: ##[J^{i},J^{j}] = i \epsilon^{ijk}J^{k}##.

I am trying to prove it. Here's my attempt. Can you please suggest the next steps?

##[J^{i},J^{j}] = J^{i}J^{j} - J^{j}J^{i} = (\epsilon^{ijk}x^{j}\nabla^{k})(\epsilon^{jki}x^{k}\nabla^{i}) - (\epsilon^{jki}x^{k}\nabla^{i})(\epsilon^{ijk}x^{j}\nabla^{k})##.

Where do I go from here?

I am trying to prove it. Here's my attempt. Can you please suggest the next steps?

##[J^{i},J^{j}] = J^{i}J^{j} - J^{j}J^{i} = (\epsilon^{ijk}x^{j}\nabla^{k})(\epsilon^{jki}x^{k}\nabla^{i}) - (\epsilon^{jki}x^{k}\nabla^{i})(\epsilon^{ijk}x^{j}\nabla^{k})##.

Where do I go from here?